Institutional environment of modern land relations - Sakal, О.; Kolisnyk, G.; Kharytonenko, R. (Land Management, Cadastre and Land Monitoring, 2022)
The expediency of reviewing the development of the institutional environment of modern land relations has been established, as it is the main factor in the formation of a new paradigm of land management development. Institutions that together form the institutional environment of land relations according to the formal approach are proposed and characterized: institute of land ownership, institute of land use law, institute of land use payment, institute of municipality, institute of state control, institute of land accounting, institute of land use for agriculture, institute land use, institute of communication. It is established that long-term dynamic processes of interaction in land relations, revision and improvement of the institutional environment need to be modernized through the implementation of new institutions. It is emphasized that the trends of economic development and productive forces require a review of the balance of economic, environmental and social priorities related to sustainable use, protection and reproduction of land potential, which can be realized through land management measures. It is determined that at the state, regional and local levels the same institutions that affect land relations have different tasks, content and tools for the implementation of their powers in terms of use, protection and reproduction of land potential.Key words: institutional environment, land relations, formal institutions, informal institutions, land management.